Cell-Free Synthetic Biology - Hong, Seok Hoon (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Cell-free synthetic biology is in the spotlight as a powerful and rapid approach to characterize and engineer natural biological systems. The open nature of cell-free platforms brings an unprecedented level of control and freedom for design compared to in vivo systems. This versatile engineering toolkit is used for debugging biological networks, constructing artificial cells, screening protein library, prototyping genetic circuits, developing new drugs, producing metabolites, and synthesizing complex proteins including therapeutic proteins, toxic proteins, and novel proteins containing non-standard (unnatural) amino acids. The book consists of a series of reviews, protocols, benchmarks, and research articles describing the current development and applications of cell-free synthetic biology in diverse areas.